2021
DOI: 10.1097/meg.0000000000001906
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence can increase the detection rate of colorectal polyps and adenomas: a systematic review and meta-analysis

Abstract: Colonoscopy is an important method to diagnose polyps, especially adenomatous polyps. However, the rate of missed diagnoses is relatively high. In this study, we aimed to determine whether artificial intelligence (AI) improves the polyp detection rate (PDR) and adenoma detection rate (ADR) with colonoscopy. We performed a systematic search in PubMed, Cochrane Library, Embase, and Web of Science databases; the search included entries in the databases up to and including 29 February 2020. Five articles that invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…AI has established its utility with numerous luminal and extra-luminal applications in gastroenterology. Recent pooled studies have established its superior detection capabilities [30][31][32][33][34], and our study echoes the superior ADR and PDR rates of AI systems. Additionally, we included all prior studies to date and completed an in-depth subgroup analysis to parse out information based on colonic segments, size, and shape not described in other pooled studies.…”
Section: Discussionsupporting
confidence: 73%
“…AI has established its utility with numerous luminal and extra-luminal applications in gastroenterology. Recent pooled studies have established its superior detection capabilities [30][31][32][33][34], and our study echoes the superior ADR and PDR rates of AI systems. Additionally, we included all prior studies to date and completed an in-depth subgroup analysis to parse out information based on colonic segments, size, and shape not described in other pooled studies.…”
Section: Discussionsupporting
confidence: 73%
“…BPPS is an effective and reliable bowel preparation scale that reflects the cleanliness of the colon during colonoscopy [36]. The meta-analysis of Li et al found that better bowel preparation can increase the detection rate based on cases without AI assistance [37]. However, despite adequate bowel preparation, residual colonic fluid can still lead to visual disruption and mucosal visibility compromise [38].…”
Section: Discussionmentioning
confidence: 99%
“…Li and colleagues published a meta-analysis in 2021 that employed a total of five studies with 4311 patients that fulfilled the selection criteria; their results showed that the ADR and PDR with the assistance of AI had a pooled OR of 1.91 (95% CI=1.68–2.16) and 1.75 (95% CI=1.52–2.01), respectively. They found that the morphology of adenomas and polyps in colonoscopy impacted detection rates and the characteristics likely influenced the results 28 . Hassan and colleagues included five RCTs with 4356 patients.…”
Section: Discussionmentioning
confidence: 99%